Jihad Fi Sabilillah of Acehnese Women against Occupation; Inspiration for the Resilience of Women during Conflicts, Tsunamis, and Pandemics - Munawiah Abdullah; Rashidah binti Mamat; Nor Azlah Sham binti Rambely; Ernita Dewi (Millati: Journal of Islamic Studies and Humanities, 2023)
AbstractThe existence of Acehnese women has an extraordinary place in the public sphere. The study aims to describe the jihad fi Sabilillah of Acehnese women against colonialism, which inspired women’s resilience during the conflict, tsunami, and Covid-19 pandemic. The greatness of Acehnese women has been known to the world for centuries for their toughness in various fields, such as the military, politics, government, and religion. Aceh is always said to have given birth to fighters who fought colonialism, such as Laksamana Malahayati, Cut Nyak Dhein, Cut Mutia, et al. The Aceh conflict significantly impacted the heroism of Acehnese women against Dutch colonialism and the spirit of the Sabil War. During the conflict, Acehnese women were actively involved in various activities. When the tsunami occurred, women also participated in resolving the impacts arising from the disaster. The Covid-19 pandemic has also had a huge impact on women. And Acehnese women’s resilience was tested when facing the pandemic until the pandemic was over. The process of gathering resource persons in the paper was through documentation review and interviews with women directly involved in the events during the conflict, tsunami, and the COVID-19 pandemic. The study results show that Acehnese women are known for being brave, being shields (protectors/fortresses of the family) during times of crisis, and never giving up, especially if the resistance is in upholding or defending religion and protecting the family and nation.Keywords: Jihad Fi Sabilillah, The Toughness of Aceh's women, conflict, Tsunami, Pandemic.AbstrakEksistensi perempuan Aceh memiliki tempat yang sangat spesial dalam ranah publik. Kajian ini bertujuan mendeskripsikan tentang jihad fisabilillah perempuan Aceh dalam melawan penjajahan manjadi inspirasi ketanguhan perempuan di masa konflik, tsunami dan pandemi covid-19.  Kehebatan perempuan Aceh telah dikenal di mata dunia sejak berabad-abad yang lalu, ketangguhan mereka dalam berbagai bidang, seperti militer, politik dan pemerintahan serta bidang agama. Aceh selalu disebut telah melehirkan pejuang-pejuang yang ikut berperang melawan penjajahan seperti Laksama Malahayati, Cut Nyak Dhein,Cut Mutia dan lain-lain. Konflik Aceh  mimiliki pengaruh yang sangat besar dengan tokoh heroisme perempuan Aceh melawan penjajahan Belanda dan semangat hikayat perang sabil. Masa Konflik  Perempuan Aceh terlibat aktif dalam berbagai kegiatan, ketika tsunami terjadi, perempuan juga berada di depan untuk menyelesaikan berbagai dampak yang muncul akibat dari bencana. Pandemi covid juga memberi pengaruh besar bagi perempuan, dan ketahanan perempuan Aceh sangat teruji untuk menghadapi wabah, sampai wabah berlalu. Proses pengumpulan sumber dalam tulisan ini melalui telaah dokumentasi,dan wawancara dengan perempuan yang terlibat langsung dalam peristiwa, masa konflik, tsunami dan pandemi. Hasil penelitian menujukkan perempuan Aceh dikenal dengan pemberani, menjadi tameng (pelindung/benteng keluarga) masa krisis dan pantang menyerah lebih-lebih kalau perlawanan yang dilakukakan dalam menegakkan atau membela agama, demikian juga dalam membela keluarga dan bangsa.Kata Kunci: Jihad Fisabilillah, Ketangguhan Perempuan Aceh, konflik, Tsunami, dan Pandemi.